Initial Outcomes of Single versus Multiple-Plug Osteochondral Allograft Transplantation for Osteochondral Defects of the Knee: A Matched Cohort Analysis - Retzky, Julia S.; Coxe, Francesca R.; Ammerman, Brittany; Neijna, Ava G.; Hinkley, Paige; Gomoll, Andreas H.; Strickland, Sabrina M. (The Journal of Knee Surgery, 2024)
Although several prior studies have described the outcomes of osteochondral allograft (OCA) transplantation for single osteochondral lesions, there is a paucity of comparative data on outcomes of single versus multiple OCA transplants. We aimed to describe the initial outcomes of single-plug versus multiple-plug knee OCA transplants at a minimum of 1 year of follow-up. We hypothesized that there would be no difference in patient-reported outcome measures (PROMs) between patients undergoing single-plug and multiple-plug OCA transplants at a minimum of 1 year of follow-up. We retrospectively reviewed the prospectively collected data of patients undergoing OCA transplantation for large (>2 cm2) osteochondral defects of the knee. Thirty patients who underwent multiple-plug (2 + ) OCA transplants (either single surface using the snowman technique or multi-surface) were 1:1 age, sex, and body mass index (BMI) matched with 30 patients who underwent single-plug OCA transplants. PROMs, including the International Knee Documentation Committee (IKDC) and Knee Injury and Osteoarthritis Outcome Score (KOOS) subscores, were obtained both preoperatively and at a minimum of 1 year postoperatively. Failure was defined as a revision OCA or conversion to unicompartmental knee arthroplasty (UKA) or total knee arthroplasty (TKA). The cohort comprised 30 females (31 affected left knees), with an average age of 37 ± 10.3 years and median follow-up of 2.0 years (interquartile range: 1.7–2.5 years). There was a significant increase in PROMs from the preoperative to the postoperative period for the entire cohort and the single-plug versus multiple-plug subgroups (p < 0.01). There was no difference between the groups with respect to the percentage of patients who achieved the minimal clinically important difference (MCID) for each PROM (p > 0.05). There were two failures, both in the single-plug group, with a mean time to failure of 3.5 years. There was no difference in the initial outcomes between patients undergoing single-plug versus multiple-plug OCA transplant at the short-term follow-up.Level of Evidence: Level IV, case series.
Keywords: knee; patella; knee, articular cartilage; knee, general